ESTIMATION OF CARBON STORAGE POTENTIAL IN THE MANGROVE FOREST REHABILITATION AREA IN SEBELE VILLAGE, RIAU ISLANDS - Lestari, Indri; Arief, Mochamad Candra Wirawan; Mulyani, Yeni; Ismail, Mochamad Rudyansyah; Widyasthana, Ferdiansyah Naufal (Jurnal Perikanan Unram, 2025)
Global warming is a phenomenon of increasing the average temperature of the earth's surface. Carbon can be stored in various forms in ecosystems, one of which is the concept of blue carbon. This research aims to analyze the condition of the mangrove ecosystem and the potential for carbon storage in the mangrove forest rehabilitation area in Sebele Village, Karimun Regency, Riau Islands. This research was conducted from October 2024 to July 2025 in the mangrove forest rehabilitation area of Sebele Village, Riau Islands Province. The method used in this research is the survey method. Standing biomass data was obtained using allometric equations. The research results show that the level of tree density in the mangrove forest rehabilitation area of Sebele Village is in the Sparse category. At the tree level, it is dominated by the Xylocarpus granatum species, while at the sapling level it is dominated by the Rhizophora mucronataspecies. The highest carbon storage value is found in the Avicennia marina species with a carbon storage value of 14.44 tons/ha. And the potential carbon storage from the calculation results obtained a carbon storage value of 61.43 tons/ha. The carbon storage value is directly proportional to the standing biomass. The greater the standing biomass, the greater the carbon stored.